2002
DOI: 10.1053/joca.2001.0482
|View full text |Cite
|
Sign up to set email alerts
|

Dedifferentiation-associated changes in morphology and gene expression in primary human articular chondrocytes in cell culture

Abstract: Our data support the hypothesis that HACs dedifferentiate when grown in monolayer cultures. Moreover, the expression patterns also show that proliferation and differentiation are exclusive features of human chondrocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
363
1
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 521 publications
(384 citation statements)
references
References 24 publications
14
363
1
6
Order By: Relevance
“…Additionally, MSC can be expanded extensively in vitro whilst chondrocytes hold a limited culture growth capacity and display phenotypic instability during the course of their expansion in monolayer culture. Such phenotypic instability (also called ''dedifferentiation'') is characterised by a shift of cellular morphology from a rounded to the typical fusiform fibroblastic shape, among other features (Schnabel et al 2002), as we also observed in the present study (Fig. 1i).…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, MSC can be expanded extensively in vitro whilst chondrocytes hold a limited culture growth capacity and display phenotypic instability during the course of their expansion in monolayer culture. Such phenotypic instability (also called ''dedifferentiation'') is characterised by a shift of cellular morphology from a rounded to the typical fusiform fibroblastic shape, among other features (Schnabel et al 2002), as we also observed in the present study (Fig. 1i).…”
Section: Discussionsupporting
confidence: 85%
“…This construct can either be delivered to and retained within the damaged site or CONTACT Mohsen Sheykhhasan m.sheykhhasan@acecr.ac.ir pre-cultured to generate the needed tissue which is later transplanted to the needed location. Thus, the choice of suitable cells and scaffolds is the major challenge in TE (Schnabel et al 2002;Tuan 2004;Tögel & Westenfelder 2007;Stocum & Zupanc 2008). The appropriate cells intended for cell therapy must have certain characteristics: they should be relatively easily available, safe, and demonstrate efficiency in the stimulation of reparation of different tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Phenotypic changed are accompanied with switches in gene expression, including loss of collagens type II, IX and XI and aggrecan and concomitant upregulation of collagen type I, III and V [96,97].…”
mentioning
confidence: 99%